(untitled) (Communications in Mathematical Research, 2019)
In this paper, some new criteria for univalence of analytic functions defined in the unit disk in terms of two parameters are presented. Moreover, the related result of Aharonov and Elias (Aharonov D, Elias U. Univalence criteria depending on parameters. Anal. Math. Phys., 2014, 4(1-2): 23–34) is generalized.